FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS NASABAH DI KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) KHIDMATUL UMMAH CABANG PAMIJAHAN BOGOR - Putirai, Riki; Trihantana, Rully; Anwar, Miftakhul (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
Since 2015, the performance of KSPPS Khidmatul Ummah has continued to show significant improvement. Still in 2015 KSPPS Khidmatul Ummah received a Cooperative Certificate. Then in 2016 he received a certificate for outstanding cooperatives and MSMEs from the Regent of Bogor, received an award for implementing RAT Activities for the 2019 Fiscal Year, received a certificate of award for superior cooperatives at the Bogor Regency level in 2019, and received an operations ranking certificate with AAB qualifications and predicate. Competition is very tight with the increasing number of sharia financial institutions nowadays, so KSPPS Khidmatul Ummah must know consumer behavior in making decisions to become customers of sharia financial institutions. Based on this, this research aims to analyze the factors that influence customer loyalty at the KSPPS Khidmatul Ummah Pamijahan Bogor Branch Office. Based on the research conducted, it is known that the service factor is the first dominant factor that influences customer loyalty at KSPPS Khidmatul Ummah Pamijahan Bogor Branch Office with a variance of 26,658%.